2000
DOI: 10.3310/hta4240
|View full text |Cite
|
Sign up to set email alerts
|

Outcome measures for adult critical care: a systematic review.

Abstract: et al. Outcome measures for adult critical care: a systematic review. Health Technol Assess 2000;4(24). Health Technology Assessment is indexed in Index Medicus/MEDLINE and Excerpta Medica/ EMBASE. Copies of the Executive Summaries are available from the NCCHTA website (see overleaf). NHS R&D HTA Programme T he overall aim of the NHS R&D Health Technology Assessment (HTA) programme is to ensure that high-quality research information on the costs, effectiveness and broader impact of health technologies is produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
84
0
7

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(93 citation statements)
references
References 272 publications
(621 reference statements)
2
84
0
7
Order By: Relevance
“…In fact, our group used this instrument in the validation of our own QOL questionnaire (14). The wide assessment and testing of the GOS is documented in the reviews of both Hayes et al (36) and Teasdale et al (37). A high interobserver reproducibility between research psychologists and research nurses has been reported, with an agreement of 92% (kappa, 0.89) (38).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, our group used this instrument in the validation of our own QOL questionnaire (14). The wide assessment and testing of the GOS is documented in the reviews of both Hayes et al (36) and Teasdale et al (37). A high interobserver reproducibility between research psychologists and research nurses has been reported, with an agreement of 92% (kappa, 0.89) (38).…”
Section: Methodsmentioning
confidence: 99%
“…Although the responsiveness or capacity to detect changes of the GOS is inferior to that of instruments that evaluate multiple QOL dimensions, its application requires less time and effort. The GOS has been widely used in the clinical setting, not only in head-injury patients but also in neurologic patients and in critical care patients in general, as shown in the exhaustive review by Hayes et al (36). In fact, our group used this instrument in the validation of our own QOL questionnaire (14).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Activities of daily living and instrumental activities of daily living [88,89] Can obtain from multiple sources with some evidence of patient-proxy agreement in ICU patients [95] Return to work/prior activity Commonly used measure Patient-centered Lacks standardized definition but used in many studies [132] Living location Same as above Suggested measures to assess impact of nutrition and exercise interventions on participant restriction at home or usual care setting after discharge from acute care hospital. [110] Has established population norms/utilities [111] Requires licensing fee EQ-5D (3-level or 5-level)…”
Section: Measure Selected Commentsmentioning
confidence: 99%
“…Für die wissenschaftliche und vergleichende Analyse der Lebensqualität ist es wichtig, standardisierte Instrumente zu haben, mit denen man die HRQL messen kann[9]. In den vergangenen Jahren wurden deswegen verschiedene standardisierte und validierte Fragebögen eingesetzt, um die Lebensqualität ehemaliger Intensivpatienten zu studieren[10]. Die 4 wichtigsten dieser Fragebögen sind:…”
unclassified